Creative economy as a growth driver: world and russian experience - S. K. Novikova (Новые технологии)
The article consideres the nature and concepts of a creative economy, identifies the prerequisites, key factors and intermediate results of formation of creative industries abroad and in Russia. The priority of creative industries in the national policy of Great Britain has become a response to the crisis in 1980s. The support for self-organizing economic clusters of artists, cinematographers, architects, creators of advertising and media content, computer games and software made it possible to generate an innovative supply on the global market of labor division and to bring the country out of crisis. Not only European and developed Asian countries followed Great Britain, but so did Australia, the USA, New Zealand, and Canada. The phenomenon of creative economics is carefully studied to identify the most effective models and strategies for shaping the conditions under which the intellectual components of the capital and labor are factors of innovation, which make it possible to take the countries to the big leagues. In this regard, there is an increase in the importance of ideas, intellectual resources, the ability of individuals to solve emerging and potential problems innovatively, with a high degree of competitiveness and obtaining additional economic and social effects. The creative economy creates conditions for the diversification of the economies of not only developed but also developing countries creating new directions of productive economic activity.